La casa, il bosco, il giardino - Gibellini, Cecilia (Archivio d’Annunzio, 2023)
Gabriele d’Annunzio made his debut as a playwright with Sogno d’un mattino di primavera, a symbolist work based on the figure of the protagonist, Isabella, who had gone mad after holding in her arms all night long her lover killed by her husband: now she feels like a vegetable creature, and she would like to blend in with the flowers in the garden and the plants in the woods. The essay shows that the three parts of the scene – the house, the garden and the wood – represent the place of confrontation and clash between the laws of men, which impose fidelity and forbid adultery, and the laws of nature, in which instinct and desire for free love dominate.